ANALISIS PEMANFAATAN DANA BANTUAN GUNA MENINGKATKAN SISA HASIL USAHA PADA KSU MAJU BERSAMA DI KABUPATEN SORONG - Anthoneta Kopong; Paulus Perey Untajana (LPPM Politeknik Saint Paul Sorong, 2019)
This study aims to determine the level of ability to obtain residual business results before and after assistance. The sample in this study is financial data according to the results of the 2015 to 2019 RAT (Annual Member Meeting) where in 2017, KSU Maju Bersama received capital assistance from the government, namely in 2017 of IDR 50,000,000, 2018 of IDR 50,000,000 and year 2019 amounting to IDR 20,000,000.- IDR 20,000,000.- The analysis shows that the gross margin ratio has decreased from 2015 - 2017, in which 2017 is the year of disbursement of early stage assistance funds. As the basic year for providing assistance, it can be seen that there was an increase in the gross margin ratio in 2018 - 2019. Before providing assistance from BUMN, the operating profit ratio obtained was relatively small. namely 1.45% in 2015 and 1.33% in 2016. In 2017 where the initial assistance was disbursed, the operating profit ratio increased to 2.17%. This means that there is a positive influence from the assistance. The net profit margin ratio was relatively small, where in 2012 and 2013 before the disbursement of aid funds, only 1.3% and 1.19%. After the disbursement of funds, there was an increase to 1.95% in 2007, 1.91% in 2015 and 1.91% in 2016. Before the disbursement of aid funds, the ROI obtained was relatively small, namely in 2015 of 2.82% and 2016 amounted to 2.49%. After the disbursement of aid funds, the ROI obtained increased to 5.54% in 2017 while in 2018 it decreased to 3.89% as a result of decreased sales and increased operating costs. In 2019 there was an increase in ROI to 4.33% as a result of increased sales. The correlation coefficient analysis obtained a coefficient of 0.0661, while the regression analysis showed that increasing the Rp. 1,000,000 assistance fund would only increase the SHU by Rp. 9,700. This shows that the relationship and influence between the use of aid funds and business results are relatively low. Or in other words, that the use of aid funds has not been managed effectively and efficiently.